Analisis Penyelesaian Soal Matematika Pada Materi Operasi Bentuk Aljabar Siswa Kelas VII SMP Muhammadiyah Silungkang - Aldo Wahyudi; Dewi Yuliana Fitri; Audra Pramita Muslim (Horizon, 2023)
This research is a quantitative descriptive study with the aim of knowing and describing students' difficulties in solving math problems in algebraic operations. The subjects in this study were class VII students, totaling 13 students. Data was collected through observation and written tests. The data collected was analyzed based on the stages of transcribing the data, coding, presenting the data and making conclusions. The results showed indications of students experiencing difficulties including, students could not understand the explanation from the teacher, when working on the questions the students looked restless and the answers of some students were disheveled and the scribbles or writings were not clear and undirected, even though the answers were close to correct. From the results of the analysis, it was concluded that the percentage of student learning outcomes obtained 4 (four) criteria where the high criteria had a percentage of 23%, the medium criteria were 15%, the low criteria were 15% and the very low criteria were 47%. Based on the percentage of learning outcomes criteria obtained by students, the criteria are very low, namely 47% having the highest percentage among the percentages of other learning outcomes, where at a very low percentage students have a lot of difficulty in working on questions no. 2, 3 and 4, the learning indicators to be achieved are apply the concept of algebraic forms.